Atividade antimicrobiana de extratos aquosos de plantas medicinais sobre bactérias causadoras de doenças de origem alimentar - Ferreira, Maria Jaiana Gomes (2017)
Foodborne illnesses (DTA) still represent a public health problem worldwide. The resistance of microorganisms to several antibiotics has been stimulating research for the discovery of new substances with natural antimicrobial action. Plant extracts have been shown to be an excellent choice of compounds that present antimicrobial activity, including action against the pathogens of interest in the food area. This work aimed to evaluate the in vitro antimicrobial activity of aqueous extracts obtained from medicinal plants on pathogenic bacteria causing food - borne diseases. The extracts were prepared using the decoction method and the aqueous solution was lyophilized and submitted to the microdilution technique for analysis of antimicrobial activity for Listeria monocytogenes, Salmonella Enteritidis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. The aqueous extracts of the plants tested showed good results on the evaluated microorganisms. The antimicrobial activity found is associated with the presence of metabolites in each sample. The concentration of extracts was higher for gram-negative than gram-positive bacteria, emphasizing that the cellular structure of these micro-organisms become them more resistant to antimicrobial substances. Extracts from the Myracrodruon urundeuva leaf and the stem bark of Croton blanchetianus showed better results, being effective on all microorganisms tested in low concentrations. For the extract of the bark of the Myracrodruon urundeuva stem only antimicrobial activity on E. coli was not verified. The stem bark extract of Croton nepetaefolius presented inhibitory and bactericidal activity against S. aureus and S. Enteritidis and only inhibitory for L. monocytogenes. The extract of the stem bark of Amburana cearensis was effective only on L. monocytogenes and S. aureus. The leaf extract of Sideroxylon obtusifolium was not effective only on E. coli and P. aeruginosa. Pterodon emarginatus seed extract was inhibitory and bactericidal on L. monocytogenes and S. aureus, but only inhibitory against S. Enteritidis. In view of this, Myracrodruon urundeuva, Sideroxylon obtusifolium, Amburana cearensis, Croton blanchetianus, Croton nepetaefolius and Pterodon emarginatus appear as a new source of substances with antibiotic potential for application in the food industry